MONITORING VARIABILITAS PROSES BERDASARKAN STATISTIK WILKS - Suci Barlian Sari; Erna Tri Herdiani; Nasrah Sirajang (Jurnal Matematika, Statistika dan Komputasi, 2019)
In a manufacturing industry quality problems often occur. One of the main cause is due to variability process. Variability process is a variation that occurs in the process, both in manufacturing and non-manufacturing processes. One method for monitoring variabiliti process is by using Wilks Statistics. Wilks statistics is a method that is used based on individual observations. This study aims to monitor the variability of the process and apply it to Electric Resistance Welded (ERW) pipes with the Wilks statistical method. In addition, a capability process analysis is also carried out when the Wilks control chart has been controlled. The result showed that all observations carried out individually were in control limit with a capability process of  2.5386, which means the process capability of ERW pipe production using a multivariate Wilks statistical control chart was capable and match  with the specifications limit specified by company.